Mass deworming to improve developmental health and wellbeing of children in low-income and middle-income countries: a systematic review and network meta-analysis - Vivian A Welch, DrPhD; Elizabeth Ghogomu, MSc; Alomgir Hossain, PhD; Shally Awasthi, MD; Zulfiqar A Bhutta, ProfMD; Chisa Cumberbatch, MSc; Robert Fletcher, MD; Jessie McGowan, PhD; Shari Krishnaratne, MSc; Elizabeth Kristjansson, PhD; Salim Sohani, MBBS; Shalini Suresh, HBSc; et al. (Elsevier, 2017)
Summary: Background: Soil-transmitted helminthiasis and schistosomiasis, considered among the neglected tropical diseases by WHO, affect more than a third of the world's population, with varying intensity of infection. We aimed to evaluate the effects of mass deworming for soil-transmitted helminths (with or without deworming for schistosomiasis or co-interventions) on growth, educational achievement, cognition, school attendance, quality of life, and adverse effects in children in endemic helminth areas. Methods: We searched 11 databases up to Jan 14, 2016, websites and trial registers, contacted authors, and reviewed reference lists. We included studies published in any language of children aged 6 months to 16 years, with mass deworming for soil-transmitted helminths or schistosomiasis (alone or in combination with other interventions) for 4 months or longer, that reported the primary outcomes of interest. We included randomised and quasi-randomised trials, controlled before-after studies, interrupted time series, and quasi-experimental studies. We screened in duplicate, then extracted data and appraised risk of bias in duplicate with a pre-tested form. We conducted random-effects meta-analysis and Bayesian network meta-analysis. Findings: We included 52 studies of duration 5 years or less with 1 108 541 children, and four long-term studies 8-10 years after mass deworming programmes with more than 160 000 children. Overall risk of bias was moderate. Mass deworming for soil-transmitted helminths compared with controls led to little to no improvement in weight over a period of about 12 months (0·09 kg, 95% credible interval [CrI] −0·09 to 0·28; moderate certainty evidence) or height (0·07 cm, 95% CrI −0·10 to 0·24; moderate certainty evidence), little to no difference in proportion stunted (eight fewer per 1000 children, 95% CrI −48 to 32; high certainty evidence), cognition measured by short-term attention (−0·23 points on a 100 point scale, 95% CI −0·56 to 0·14; high certainty evidence), school attendance (1% higher, 95% CI −1 to 3; high certainty evidence), or mortality (one fewer per 1000 children, 95% CI −3 to 1; high certainty evidence). We found no data on quality of life and little evidence of adverse effects. Mass deworming for schistosomiasis might slightly increase weight (0·41 kg, 95% CrI −0·20 to 0·91) and has little to no effect on height (low certainty evidence) and cognition (moderate certainty evidence). Our analyses do not suggest indirect benefits for untreated children from being exposed to treated children in the community. We are uncertain about effects on long-term economic productivity (hours worked), cognition, literacy, and school enrolment owing to very low certainty evidence. Results were consistent across sensitivity and subgroup analyses by age, worm prevalence, baseline nutritional status, infection status, impact on worms, infection intensity, types of worms (ascaris, hookworm, or trichuris), risk of bias, cluster versus individual trials, compliance, and attrition. Interpretation: Mass deworming for soil-transmitted helminths with or without deworming for schistosomiasis had little effect. For schistosomiasis, mass deworming might be effective for weight but is probably ineffective for height, cognition, and attendance. Future research should assess which subset of children do benefit from mass deworming, if any, using individual participant data meta-analysis. Funding: Canadian Institutes of Health Research and WHO.